Facile fabrication, mechanical property and flame retardancy of aerogel composites based on alginate and melamine-formaldehyde. (24th October 2019) - Li, Xin-Lei; He, Yan-Rong; Qin, Zi-Ming; Chen, Ming-Jun; Chen, Hong-Bing
Abstract: Aerogel composites based on melamine-formaldehyde (MF) and alginate (A) was fabricated with ice-templated method. The preparation process involves two cross-linking processes, in aerogel precursor at room temperature and in dried aerogel at 80 °C (100% humidity), respectively. Cross-linking was demonstrated to be very efficient for improving the mechanical property and water resistance of MF-A aerogels. The obtained aerogels have compressive moduli ranging from 1.2 MPa to 24.1 MPa. All the cross-linked aerogels display good dimensional stability when soaked in water. The morphological study of MF-A aerogels show a layered or network microstructure, with a homogeneous distribution of MF spheres. Due to low density and porous structure, MF-A aerogels have low thermal conductivity from 0.035 to 0.047 W/m K. MF-A aerogels have good thermal stability and extremely low flammability, with LOI value up to 41%. This novel aerogel from partially bio-based raw material would have promising application prospects. Graphical abstract: Image 10735 Highlights: Fully organic aerogel based on melamine-formaldehyde and alginate was fabricated. The resulting flame retardant aerogels possess low thermal conductivity. The obtained aerogels are insoluble in water even fabricated from water solution.